Navigating the combinations of platelet-rich fibrin with biomaterials used in maxillofacial surgery - Ieviņa, Lauma; Dubņika, Arita (Frontiers in Bioengineering and Biotechnology, 2024)
Platelet-rich fibrin (PRF) is a protein matrix with growth factors and immune cells extracted from venous blood via centrifugation. Previous studies proved it a beneficial biomaterial for bone and soft tissue regeneration in dental surgeries. Researchers have combined PRF with a wide range of biomaterials for composite preparation as it is biocompatible and easily acquirable. The results of the studies are difficult to compare due to varied research methods and the fact that researchers focus more on the PRF preparation protocol and less on the interaction of PRF with the chosen material. Here, the literature from 2013 to 2024 is reviewed to help surgeons and researchers navigate the field of commonly used biomaterials in maxillofacial surgeries (calcium phosphate bone grafts, polymers, metal nanoparticles, and novel composites) and their combinations with PRF. The aim is to help the readers select a composite that suits their planned research or medical case. Overall, PRF combined with bone graft materials shows potential for enhancing bone regeneration both in vivo and in vitro. Still, results vary across studies, necessitating standardized protocols and extensive clinical trials. Overviewed methods showed that the biological and mechanical properties of the PRF and material composites can be altered depending on the PRF preparation and incorporation process.